Exploring the Diversity and Distribution of Neotropical Avian Malaria Parasites – A Molecular Survey from Southeast Brazil - Lacorte, Gustavo A.; Félix, Gabriel M. F.; Pinheiro, Rafael R. B.; Chaves, Anderson V.; Almeida-Neto, Gilberto; Neves, Frederico S.; Leite, Lemuel O.; Santos, Fabrício R.; Braga, Érika M. (PloS one, 2013)
Southeast Brazil is a neotropical region composed of a mosaic of different tropical habitats and mountain chains, which allowed for the formation of bird-rich communities with distinct ecological niches. Although this region has the potential to harbor a remarkable variety of avian parasites, there is a lack of information about the diversity of malarial parasites. We used molecular approaches to characterize the lineage diversity of Plasmodium and Haemoproteus in bird communities from three different habitats in southeast Brazil based on the prevalence, richness and composition of lineages. We observed an overall prevalence of 35.3%, with a local prevalence ranging from 17.2% to 54.8%. Moreover, no significant association between prevalence and habitat type could be verified (p>0.05). We identified 89 Plasmodium and 22 Haemoproteus lineages, with 86% of them described for the first time here, including an unusual infection of a non-columbiform host by a Haemoproteus (Haemoproteus) parasite. The composition analyses of the parasite communities showed that the lineage composition from Brazilian savannah and tropical dry forest was similar, but it was different from the lineage composition of Atlantic rainforest, reflecting the greater likeness of the former habitats with respect to seasonality and forest density. No significant effects of habitat type on lineage richness were observed based on GLM analyses. We also found that sites whose samples had a greater diversity of bird species showed a greater diversity of parasite lineages, providing evidence that areas with high bird richness also have high parasite richness. Our findings point to the importance of the neotropical region (southeast Brazil) as a major reservoir of new haemosporidian lineages.